Nucleolar protein 6 as a potential oncogenic factor in colorectal cancer - Shunxin Song; Yixin Zhang; Lingxi Li; Kaikai Zhou; Yuguo Zhao; Zhao Yang; Shuohao Guo; Rongzhang He; Jianwen Zhang (PLoS ONE, 2026)
Background Colorectal cancer (CRC) is a common malignancy of the digestive tract associated with high mortality rates and significant invasive properties. Despite advancements in research, a comprehensive understanding of the regulatory mechanisms underlying CRC remains elusive. Objective This study aimed to investigate the potential role of nucleolar protein 6 (NOL6) and its related genes as novel biomarkers for cell proliferation in CRC. The findings of this study could significantly contribute to early diagnosis and more effective therapeutic strategies for CRC. Methods Human CRC cell line HCT116 was cultured under standard conditions. Quantitative real-time polymerase chain reaction and immunohistochemistry analysis were used to measure NOL6 expression levels in CRC tissues. Cell proliferation was assessed using the MTT assay, Celigo cell count assay, and colony formation assays, while flow cytometry was employed to evaluate cell apoptosis. Additionally, a transwell migration assay was performed to evaluate CRC cell migration and invasion. Comprehensive proteomic and transcriptomic analyses were performed to identify the downstream genes and pathways affected by NOL6 knockdown. The expression of these genes was further validated by Western blotting. Xenograft mouse models were used to determine the effects of NOL6 on CRC in vivo . Tandem mass tags (TMT)-labeled quantitative proteomic technology and bioinformatic analysis were employed to identify the functional pathway and proteins regulated by NOL6. Results The Cancer Genome Atlas data analysis revealed a significant upregulation of NOL6 in CRC cells compared with adjacent normal cells. In HCT116 cells, downregulation of NOL6 was associated with decreased proliferation and colony formation, as well as increased apoptosis. Additionally, NOL6 knockdown resulted in a decrease in the weight and volume of tumors in nude mice, suggesting its role in tumorigenesis. TMT and Western blot analyses revealed that NOL6 knockdown suppressed MCM3 and MCM7 expression. Conclusion This study demonstrated that NOL6 functions as an oncogene that facilitates CRC progression, suggesting its potential role as a therapeutic target for CRC management.